Impacto de fontes de nitrogênio no crescimento e metabolismos do nitrogênio e antioxidante em plantas jovens de milho (Zea mays) cultivadas em substrato contendo rejeito de mineração - Souza, Thaiara de (2020)
The objective of this work was to study the impact of different sources of nitrogen on the growth and metabolism of nitrogen and antioxidants in young plants of corn (Zea mays) cultivated in substrate containing mining waste. In this way, corn seeds (Cultivar Lavrador) were sown in 1 liter pots with substrate containing mining waste, resulting from the rupture of the Fundão dam (Mariana - MG) and 3:1 sand, respectively. Four treatments were tested with 8 repetitions, varying the nitrogen source in the recommended dose for corn of 100 kg ha-1. The nitrogen sources used were ammonium sulfate (treatment with ammonium), calcium nitrate (treatment with nitrate), ammonium nitrate (treatment with ammonium and nitrate) and treatment without a nitrogen source (S/ N). Nitrogen and antioxidant metabolisms were evaluated, as well as growth. The results showed that plants cutivated in the substrate containing only NO3- showed greater growth in height and diameter. For number of leaves and root length, the treatment with NH4+ showed higher values. Chlorophyll a and b the highest levels found were in the NH4+ and NH4+/NO3-treatments. For carotenoids, the lowest content observed was in the treatment with NO3-. For total nitrogen content, the treatment with the highest content was NH4+, for both leaves and roots. The activity of the nitrate reductase enzyme did not differ according to the nitrogen source, in roots. In leaves the greatest activity was observed in the treatment with NO3-. In roots, the activity of the GS enzyme did not differ due to the nitrogen source and was low, however the activity was more present in the leaves and differed in the treatment with NH4+/ NO3-. GDH activity in leaves was higher in plants cultivated with NH4+, for roots were cultivated with NO3-. For GOGAT, both leaves and roots showed greater activity with NH4+ treatment. For lipid peroxidation in leaves the treatment with NH4+/NO3- were the ones with higher values and in roots the treatments did not differ depending on the nitrogen source. The hydrogen peroxide content was higher observed and did not differ in the treatments with NO3-, NH4+/NO3- and S/ N, however in roots there were no differences. The SOD activity on the leaves did not differ according to the nitrogen source, in roots, it was higher in the S/ N treatment. The S/ N treatment increased the APX activity in the leaves, in roots the greatest activity occurred in the NH4+ treatment. The activity of CAT in leaves did not differ according to the nitrogen source and in roots the greatest activity was observed in the substrate with NO3-.